Human papillomavirus in canine serum: evidence from a Chinese study - Liu, Yumeng; Xie, Lulu; Zhou, Yimin; Zhou, Lin; Bi, Jingshan; Zheng, Min; Lan, Tian; Sun, Wenchao (Frontiers in Veterinary Science, 2025)
IntroductionHuman papillomaviruses (HPVs) are well-known for causing both benign and malignant epithelial growths in humans, but their occurrence in non-human species is rarely reported. Expanding the understanding of HPV’s host range is essential for assessing its ecological and public health implications.MethodsWe investigated serum samples from dogs collected in Guangxi, China, between 2014 and 2020. PCR screening was performed to detect HPV DNA, followed by sequencing and phylogenetic analysis of the positive amplicons.ResultsHPV DNA was unexpectedly detected in 2 out of 1,226 canine serum samples, yielding a detection rate of 0.16%. Phylogenetic analysis revealed that the sequences clustered with alpha2-HPV78 (GX-70-related) and alpha2-HPV94 (GX-47-related), respectively. Interestingly, both sequences displayed multiple amino acid variations in viral proteins. However, virus isolation was not achieved.DiscussionThe detection of HPV nucleic acids in canine serum suggests a potential presence of HPV in canine hosts. These findings provide new insights into the possible host range of HPV, underscoring the need for further research to assess the virus’s infectivity, transmission dynamics, and implications for both animal and human health.